Pengaruh Kompetensi Kepribadian Guru Terhadap Pembentukan Karakter Setingkat Sekolah Menengaah Atas - Nur Nabila Ilma Nafisa; Didit Darmawan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the influence of teachers' personality competencies on the formation of students' character in Senior High School (SMA). Teachers' personality competencies, such as discipline, responsibility, empathy, and example, play an important role in the character education process in schools. Teachers with positive personalities are able to create a conducive learning environment and provide good examples of behavior for students, thus helping the formation of strong and moral student character. Through social interaction in the school environment, students can develop positive attitudes, such as a sense of responsibility, hard work, honesty, and independence, which are essential for community life. This research is included in a qualitative research with a literature study approach to explore the influence of personality competence on character formation. The results of the study show that the teacher's personality competence has a significant influence on the development of students' character. The conclusion of this study is that teacher personality competence is one of the key factors in character education in high school.